Implementasi SPBE-FORGE(6D) sebagai Framework Enterprise Architecture dalam Percepatan Transformasi Digital Pemerintah Daerah - Setiawan Assegaff; Lola Yorita Astri; Kurniabudi (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
Digital transformation within local governments requires a standardized architectural framework to ensure service integration, data consistency, and efficient information technology governance. This study examines the implementation of SPBE-FORGE(6D) as an Enterprise Architecture framework designed to support the acceleration of Indonesia’s Electronic-Based Government System (SPBE). The evaluation employed Enterprise Architecture Success Metrics, including architecture artefact quality, system interoperability, application efficiency, and data consolidation indicators. The results show that SPBE-FORGE(6D) improved architecture artefact quality by 35–36%, reduced application duplication by 41%, decreased data silos by 44%, and enhanced digital service integration by 150%. These findings demonstrate that SPBE-FORGE(6D) effectively strengthens IT governance, improves cross-domain architectural integration, and significantly contributes to accelerating local government digital transformation in an efficient, standardized, and sustainable manner.